Дорадянський період розвитку інституту найвищої судової інстанції на теренах України: особливості еволюції функції - Калараш, А. А.; Kalarash, A. A. (Прикарпатський юридичний вісник. - 2019. - Вип. 1 (26), т. 3. - С. 21-29, 2019)
Проведено історично-юридичний аналіз особливостей еволюції функцій найвищої судової інстанції на теренах українських земель у період їх перебування у складі Російської імперії. Особливу увагу приділено Урядуючому Сенату у контексті його взаємовідносин з підпорядкованими судовими установами.

The article attempts an historical and legal analysis of the peculiarities of the evolution of the functions of the highest court in the Ukrainian lands during their stay in the Russian Empire. Special attention is paid to the Gov-erning Senate in the context of its relations with subordi-nate judicial institutions.This body, founded during the Petrine reforms, in-itially had a fairly broad competence, in addition to the judiciary, also having administrative and legislative functions. With the beginning of the XIX century. the competence of the Senate was significantly reduced due to the transfer of part of its functions to the General Council and ministries. However, it remained the main audit and appellate court for various courts and at the time of the reign of Alexander II was considered the supreme court of the country.The judicial reform of 1864 finally contributed to the transformation of the Senate into the Supreme Court of Cassation and the body that supervised the activities of the ranks that were in the civil service. Of particular im-portance, in our opinion, was the creation, according to the Judicial Statutes, in 1866 of criminal and civil cas-sation departments, which considered cases coming from judicial institutions created as a result of the reform, in-cluding from the territory of the Ukrainian provinces.The jurisdiction of the Senate allowed him to either leave the sentence unchanged or overturn it. The Senate acted as the highest court, its decisions were final and not subject to appeal. Objectively, this has contributed to more accurate enforcement of laws on the ground and a gradual transition to new standards of justiceю.

Проведен историко-юридический анализ особенностей эволюции функций высшей судебной инстанции на территории украинских земель в период их пребывания в составе Российской империи. Особое внимание уделено Правительствующему Сенату в контексте его взаимоотношений с подчиненными судебными учреждениями.
Pre-soviet period of development of the institute of the supreme judicial institution in Ukraine: features of the evolution of the function
Калараш, А. А. Дорадянський період розвитку інституту найвищої судової інстанції на теренах України: особливості еволюції функції / А. А. Калараш // Прикарпатський юридичний вісник. - 2019. - Вип. 1 (26), т. 3. - С. 21-29.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Історія. History. История; історико-правовий аналіз; historical and legal analysis; историко-правовой анализ; Урядуючий Сенат; Governing Senate; Правительствующий Сенат; Російська імперія; Russian Empire; Российская империя; кримінальний департамент; criminal department; уголовный департамент; цивільний департамент; civil department; гражданский департамент; касаційний департамент; cassation department; кассационный департамент; компетенція Сенату; competence of the Senate; компетенция Сената; судові установи; судочинство